Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s11060-016-2093-1
|View full text |Cite|
|
Sign up to set email alerts
|

Which elderly newly diagnosed glioblastoma patients can benefit from radiotherapy and temozolomide? A PERNO prospective study

Abstract: The role of temozolomide concurrent with and adjuvant to radiotherapy (RT/TMZ) in elderly patients with glioblastoma (GBM) remains unclear. We evaluated the outcome of patients >70 years in the context of the Project of Emilia-Romagna Region in Neuro-Oncology (PERNO), the first Italian prospective observational population-based study in neuro-oncology. For this analysis the criteria for selecting patients enrolled in the PERNO study were: age >70 years; PS 0-3; histologically confirmed GBM; postoperative radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…There have been robust efforts to decipher the molecular biomarkers of glioma and their prognostic signi cance as well as apply these ndings to clinical practice, particularly in choosing appropriate candidates for initial chemotherapy [30,[33][34][35][36][37][38]. TERT promoter mutation and MGMT methylation status are among the most important markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been robust efforts to decipher the molecular biomarkers of glioma and their prognostic signi cance as well as apply these ndings to clinical practice, particularly in choosing appropriate candidates for initial chemotherapy [30,[33][34][35][36][37][38]. TERT promoter mutation and MGMT methylation status are among the most important markers.…”
Section: Discussionmentioning
confidence: 99%
“…While the positive prognosis role of MGMT methylation in patients treated with TMZ has been observed in many studies [9,36,[53][54][55][56], there were still con icting results regarding the prognostic value of this genetic marker in GBM patients [34,57]. It raises the question that there might be other factors affecting the responsiveness to TMZ besides MGMT methylation status.…”
Section: Discussionmentioning
confidence: 99%
“…The median age at prognosis is approximately 65 years (3), and age is a poor prognostic factor. The main therapy for HGG is surgical removal; however, because of comorbidities, elderly patients are often suboptimally treated (4). After surgery, RT becomes the mainstay treatment for GB.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Elderly patients have frequently been excluded from clinical trials, 6 and those studies that do examine this population have demonstrated suboptimal survival outcomes. Chemotherapy (CT) alone, 8,9 radiotherapy (RT) alone, 10 and combined-modality therapy using CT and RT (CRT), 11,12 have all produced improved outcomes in select elderly patients. Chemotherapy (CT) alone, 8,9 radiotherapy (RT) alone, 10 and combined-modality therapy using CT and RT (CRT), 11,12 have all produced improved outcomes in select elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,7 Determining the ideal adjuvant treatment for elderly patients is further complicated by multiple treatment options. Chemotherapy (CT) alone, 8,9 radiotherapy (RT) alone, 10 and combined-modality therapy using CT and RT (CRT), 11,12 have all produced improved outcomes in select elderly patients. Age is just 1 of many factors clinicians may consider when choosing therapy for patients with GBM.…”
Section: Introductionmentioning
confidence: 99%